Digital Learning, Mediating Effect of Instructor Facility on Student Satisfaction at Universities - Sah, Gunja Kumari (MO.RI Publishing, 2024)
Digital learning is essential to explore digital platforms at university. The study considered a quantitative approach to examine the impact of digital learning on student satisfaction at various universities during COVID-19 in Nepal. The paper also focused on analyzing the mediating effect of instructor facility on student satisfaction. Several pieces of information were attained from the 225 students of Tribhuvan University, Kathmandu University, Purbanchal University, Pokhara University, and Rajarshi Janak University through stratified random sampling techniques. Data was converted into valuable information by analyzing raw data through SPSS software and used for frequency analysis and exploratory factor analysis. Next-level analysis was performed by AMOS software for structural equation modeling to examine student satisfaction with digital learning and the mediating effect of instructor facility. The result of the paper found all dimensions significantly influenced on mediating construct of instructor facility and student satisfaction. It also identified convenience as the most influential factor than technology in instructor facilities. However, the result demonstrates that technology was the most influential factor, rather than convenience, on dependent construct student satisfaction. It revealed that instructor facility significantly affects student satisfaction. So, digital learning becomes effective, and efficient, when convenient digital portals, technology facilities, instructors' knowledge, educational institution systems, and students are thoroughly engaged with it.